Pediatric dermatological vital emergencies - Chiriac, Anca; Diaconeasa, Adriana; Miulescu, Raluca; Voicu, Cristiana; Chiriac, Anca E.; Fölster-Holst, Regina; Wollina, Uwe (Aktuelle Dermatologie, 2024)
Pediatric patients in the emergency unit often present with muco-cutaneous symptoms. Most muco-cutaneous findings are not life-threatening, but it is crucial to identify those dermatoses with urgent need of treatment. In this review, we present infectious and non-infectious pediatric disorders with muco-cutaneous red-flag signs for a potential severe course and complications associated with significant mortality. By recognizing these dermatological symptoms, early confirmation of diagnosis and initiation of appropriate treatment outcome can be optimized.
Keywords: children; pediatric emergencies; dermatoses; mortality; treatment